Investigating pedagogical content knowledge-in-action - Taylan, Rukiye Didem (2017)
This article investigates the pedagogical content knowledge (PCK) of a teacher educator who teaches 5th-grade mathematics in a school in the context of a university-school partnership project. PCK is analyzed in a qualitative way through video-taped classroom episodes with focus on interactions between the teacher and the students as well as the teacher’s reflections and pedagogical reasoning on the interactions. The analyses indicate examples of PCK development during teaching, especially refinement in the domain of knowledge of instructional strategies and representations. This knowledge improved as a result of reflection on student questioning and analysis of students’ misconceptions. Different roles of being teacher, teacher educator, and researcher afforded opportunities to gain insights on how to develop knowledge required for teaching and analyze it in order to facilitate future teachers’ learning.